UNC-45A is preferentially expressed in epithelial cells and binds to and co-localizes with interphase MTs. Issue 10 (3rd October 2019) - Habicht, Juri; Mooneyham, Ashley; Shetty, Mihir; Zhang, Xiaonan; Shridhar, Vijayalakshmi; Winterhoff, Boris; Zhang, Ying; Cepela, Jason; Starr, Timothy; Lou, Emil; Bazzaro, Martina
ABSTRACT: UNC-45A is an ubiquitously expressed protein highly conserved throughout evolution. Most of what we currently know about UNC-45A pertains to its role as a regulator of the actomyosin system. However, emerging studies from both our and other laboratories support a role of UNC-45A outside of actomyosin regulation. This includes studies showing that UNC-45A: regulates gene transcription, co-localizes and biochemically co-fractionates with gamma tubulin and regulates centrosomal positioning, is found in the same subcellular fractions where MT-associated proteins are, and is a mitotic spindle-associated protein with MT-destabilizing activity in absence of the actomyosin system. Here, we extended our previous findings and show that UNC45A is variably expressed across a spectrum of cell lines with the highest level being found in HeLa cells and in ovarian cancer cells inherently paclitaxel-resistant. Furthermore, we show that UNC-45A is preferentially expressed in epithelial cells, localizes to mitotic spindles in clinical tumor specimens of cancer and co-localizes and co-fractionates with MTs in interphase cells independent of actin or myosin. In sum, we report alteration of UNC45A localization in the setting of chemotherapeutic treatment of cells with paclitaxel, and localization of UNC45A to MTs both in vitro and in vivo . These findings will be important to ongoing and future studies in the field that further identify the important role of UNC45A in cancer and other cellular processes.